Identification and determination of by‐products originating from ozonation of chlorpyrifos and diazinon in water by liquid chromatography–mass spectrometry. Issue 21 (24th September 2020) - Lee, Yunhee; Kim, Yun‐Ji; Khan, Muhammad Saiful Islam; Na, Yun‐Cheol
Abstract: The degradation of two organophosphates, chlorpyrifos and diazinon, in water using microplasma equipment to produce ozone and the identification of their products were studied by using liquid chromatography–mass spectrometry. The organophosphates gradually decreased with time and were completely removed after 10 min, and diazinon was degraded at a relatively fast rate compared to chlorpyrifos. The products formed during the process were identified and determined with accurate mass measurements and tandem mass spectrometry spectra, providing reliable structural determination. Chlorpyrifos oxon was formed through the oxidation of chlorpyrifos, followed by the formation of 3, 5, 6‐trichloro‐2‐pyridinol and diethyl phosphate by hydrolysis. Diazinon formed various products through more complicated degradation processes than those of chlorpyrifos. The major products of diazinon degradation were 2‐isopropyl‐6‐methyl‐4‐pyrimidinol and diethyl phosphate by hydrolysis after oxidation, exhibiting diazoxon as an intermediate at trace levels. Direct hydrolysis of diazinon also occurred, producing diethyl thiophosphate, which was observed at a low concentration for a transient time and exhibited a less favorable process than sequential oxidation and hydrolysis. The other products, hydroxy diazinons and hydroxy‐2‐isopropyl‐6‐methyl‐4‐pyrimidinols, formed by hydroxylation, were also identified, but they were present in low amounts. Degradation mechanisms of chlorpyrifos and diazinon were proposed with the quantitatively evaluated products.